Preparation of sulphate aluminate cement amended bentonite and its use in heavy metal adsorption. (20th May 2020) - Niu, Mengdie; Li, Guoxin; Cao, Li; Wang, Xudong; Wang, Wenzhao
Abstract: The development of environment friendly and practically feasible technologies or adsorbents to treat water pollution due to heavy metals is urgently required. Herein, Sulphate aluminate cement - bentonite (SAC-bentonite) composites were synthesized and used as low-cost and high-efficiency adsorbents to remove Cr 3+, Pb 2+, and Cd 2+ from aqueous solution. The characteristics of SAC-bentonite were analyzed via X-ray diffraction (XRD) and scanning electron microscopy (SEM). Effects of the amount of adsorbent, solution pH, and contact time on the adsorption performance of SAC-bentonite were also studied. The adsorption mechanism was analyzed via XRD, X-ray photoelectron spectroscopy (XPS), and SEM. The results demonstrate that the adsorption capacities of SAC-bentonite for Cr 3+ were similar to that of pure bentonite or pure SAC, while the adsorption capacities for Pb 2+ and Cd 2+ were significantly higher than those for bentonite or SAC. When the ratio of bentonite to SAC was 1:1, the removal efficiency of SAC-bentonite for Cr 3+, Pb 2+, and Cd 2+ was 99.956%, 99.838%, and 99.717%, respectively. The adsorption kinetics was well described by Pseudo-second-order equation. Graphical abstract: Image 1 Highlights: SAC-bentonite composites were prepared as an adsorbent for removing heavy metals. SAC-bentonite composites show an excellent adsorption of Cr 3+, Pb 2+, and Cd 2+ . The adsorption of Cr 3+, Pb 2+, and Cd 2+ was mainly attributed to cation exchange.